2022
DOI: 10.21037/apm-21-3403
|View full text |Cite
|
Sign up to set email alerts
|

Survival to hospital discharge and neurological outcomes with targeted temperature management after in-hospital cardiac arrest: a systematic review and meta-analysis

Abstract: Background: Multiple randomized controlled trials have shown that targeted temperature management (TTM) has favorable effects in out-of-hospital cardiac arrest. However, the benefit of TTM in patients with in-hospital cardiac arrest (IHCA) remains to be verified. Methods:The PubMed, Cochrane Library, and EMBASE databases were searched for clinical studies with the primary outcomes of survival to hospital discharge and neurological outcomes. Neurological outcomes were evaluated by the categorical scale of cereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
2
3
0
Order By: Relevance
“…Whether therapeutic hypothermia improves survival is controversial, especially if neurologic outcome is not favorable. Our results are similar to previous meta-analyses that demonstrated no survival benefit with hypothermia [ 18 23 , 27 ]. In parallel with the analysis by Sanfilippo and colleagues, our TSA confirmed the futility of further randomized controlled trials in respect to the mortality outcome [ 22 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Whether therapeutic hypothermia improves survival is controversial, especially if neurologic outcome is not favorable. Our results are similar to previous meta-analyses that demonstrated no survival benefit with hypothermia [ 18 23 , 27 ]. In parallel with the analysis by Sanfilippo and colleagues, our TSA confirmed the futility of further randomized controlled trials in respect to the mortality outcome [ 22 ].…”
Section: Discussionsupporting
confidence: 92%
“…Clinically, favorable neurologic outcome is defined by the mRS or CPC scores, which describe the functionality of a patient after suffering a neurologic injury [ 16 , 17 ]. Similar to previous meta-analyses, our meta-analysis revealed no overall neurologic benefit of therapeutic hypothermia when compared to normothermia [ 18 23 ]. TSA of favorable neurologic outcome demonstrated the futility of therapeutic hypothermia compared to normothermia, suggesting further randomized controlled studies should likely not be conducted with this outcome.…”
Section: Discussionsupporting
confidence: 86%
“…To our knowledge, no randomized trials of TTM for IHCA have been conducted. A meta-analysis that included six retrospective controlled studies revealed that TTM did not improve survival or neurological function among patients with IHCA [ 44 ]. Because the characteristics of patients with IHCA and the treatment received before, during, and after arrest may differ from those of patients with OHCA, the prognosis and LOS after TTM should be evaluated as different entities [ 37 , 43 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Out-of-hospital cardiac arrest (OHCA) affects over 600,000 individuals each year in the United States and Europe, while in-hospital cardiac arrest (IHCA) affects * 300,000 people a year [1], posing a major public health challenge. Mortality remains unacceptably high, with roughly one in ten OHCA and one in four IHCA patients surviving to hospital discharge [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Out-of-hospital cardiac arrest (OHCA) affects over 600,000 individuals each year in the United States and Europe, while in-hospital cardiac arrest (IHCA) affects ~ 300,000 people a year [ 1 ], posing a major public health challenge. Mortality remains unacceptably high, with roughly one in ten OHCA and one in four IHCA patients surviving to hospital discharge [ 2 5 ]. Hypoxic–ischemic brain injury (HIBI) is a major contributor to outcomes after cardiac arrest (CA) [ 6 ]; the burden of HIBI is determined by both the primary ischemic injury and the secondary brain injury after reperfusion [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%